Endothelial cell cultured on HA/TCP/chitosan scaffold for bone tissue engineering - Bachtiar EW; Amir LR; Abbas B; Utami S (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: Angiogenesis is crucial for the success of bone reconstruction through tissue engineering. Currently, is still not known the activity of endothelial cells that is responsible for blood vessel formation, cultured in HA/TCP/chitosan scaffold. The ability of the scaffold to facilitate the proliferation and migration of endothelial cell to form blood vessel is essential for cell survival especially in the inner area of the scaffold that is susceptible for cell death if adequate vascularization is not occurred. Purpose: The purpose of this study was to evaluate the porosity of HA/TCP/chitosan scaffold and the biocompatibility of HA/TCP/chitosan scaffold to endothelial cells. Methods: Endothelial cells were isolated from umbilical vein (human umbilical vein endothelial cells/ HUVEC). HA/ TCP/chitosan scaffold was made from two gelling agents and various basic washing solutions. The characteristic of scaffold was examined by scanning electron microscopy. The activity of HUVEC was evaluated by MTT assay. Results: Initial average scaffold porosity size range from 68 μm and increased up to 134 μm after 7 days incubation with 10 mg/L lysozyme. There was no significant difference in the viability of HUVEC incubated with the scaffold compared to control. Conclusion: HA/TCP/chitosan has a good biocompatibility for HUVEC. This condition supports the activity of HUVEC in the scaffold for angiogenesis process, to provide oxygen and nutrient necessary for osteoblast.Latar belakang: Angiogenesis merupakan proses yang penting untuk keberhasilan rekonstruksi tulang melalui rekayasa jaringan. Saat ini, aktifitas sel endotel pembentuk dinding pembuluh darah pada HA/TCP/chitosan scaffold belum diketahui. Kemampuan scaffold sebagai tempat proliferasi dan migrasi sel endotel untuk membentuk pembuluh darah penting untuk kelangsungan hidup sel osteoblast terutama di bagian dalam scaffold. Tujuan: Mengevaluasi porositas HA/TCP/chitosan scaffold serta sifat biokompatibilitas scaffold terhadap sel endotel. Metode: Sel endotel diisolasi dari vena tali pusat (human umbilical vein endothelial cells/HUVEC). HA/TCP/ chitosan scaffold dibuat dengan variasi gelling agents dan dicuci dengan berbagai larutan basa. Karakter scaffold dievaluasi dengan scanning electron microscope. Aktifitas HUVEC dievaluasi dengan MTT assay. Hasil: Pada tahap awal, rata-rata ukuran porus 68 μm dan meningkat menjadi 134 μm setelah inkubasi dengan 10 mg/mL lysosyme selama 7 hari. Kultur HUVEC pada scaffold selama 24 jam tidak menunjukkan tingkat viabilitas yang berbeda dibandingkan dengan kontrol. Kesimpulan: HA/TCP/chitosan memiliki sifat biokompatibilitas yang baik terhadap sel HUVEC. Kondisi ini memberikan dukungan terhadap aktifitas sel HUVEC pada scaffold untuk proses angiogenesis yang akan memberikan oksigen dan nutrisi untuk osteoblas.